(untitled) (Journal of the College of Education for Women, 2019)
Vagrancy is global problem, but its geographical distribution differs from one societyto another and from one place to another inside the same society.Till now there isn’t a real factor that can explain the phenomenon, spite that economy plays aconstituent and distinguishing part, and spite the fact that Vagrancy is considered a realdeviation that can be compared with criminality level, and cannot be separated from its effecton family, local society and school. In addition to unprecedented work under heavily pressurethat attack to a minimum protection and safety. Vagrant may be a child, a teen, a young, oreven an old man. Vagrancy thus means different people with different ages and not onlyprecisely children. Vagrant is not necessary to be a male, in modern societies the differencesbetween male and female get back to make a female vagrant as well as male but in a lower proportion compared with the female this because of some traditional controls. The main reason behind vagrancy is that family environment that has its pressures, while street has its attractive features. Inside family, poverty deprivation, drinking alcohol, cannabis, familyviolence and multi-wives ….. etc. In the street there is freedom of walking, getting foodthrough begging, far away from father stick or mother complain, inside family there isisolation, while on the street there is an open way through it there is multi elements of threatto the vagrant life, personality and future. Vagrant world is not easy, it’s in the bottom of society it like a forest full of violence and the principles of shame and cooperation collapse.